Perlindungan Hukum terhadap Pekerja Kebersihan Sampah di Kota Sorong Ditinjau dari Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Dayen Baho; Novalin M Syauta; Yonatan Tebai (Departement of Mathematics Education, 2023)
This study aims to determine the form of legal protection for waste cleaning workers according to Law Number 13 of 2003 at PT. Hendrian and obstacles in implementing legal protection for waste cleaning workers at PT. Hendrian.The research method used is, the nature of this research is normative empirical, using primary and secondary data, so that the data collection techniques are interviews, documentation, observation and literature, after obtaining the data it will be analyzed descriptively qualitatively. Based on the results of the study, it can be explained that the legal protection of waste cleaning workers by PT. Hendrian as the company that employs is still lacking, where there are still unilateral layoffs by the company and the completeness of the facilities or work equipment is still lacking, this is of course very clearly contrary to the provisions of Law Number 13 of 2003 concerning employment and obstacles in the implementation of legal protection for waste cleaning workers in PT. Hendrian, namely, the company does not carry out job socialization to workers; low level of education of workers; the workers do not understand the duties and responsibilities according to the employment contract; workers are not aware of the existence of Law Number 13 of 2003 which can be used as a guide in the event of a violation of their rights.